Efficacy of radiation exposure in laryngeal squamous cell carcinoma is mediated by the LAMP3/LAMC2/tenascin-C pathway. Issue 13 (October 2019) - Wu, Hao; Li, Juanjuan; Chen, Jianqiu; Yin, Yong; Da, Peng; Chen, Qingwen; Zhang, Zhenxin; Wang, Jinxing; Wang, Guohua; Qiu, Xiaoxia
The present study explored the role of LAMP3 and related molecular mechanisms in the efficacy of radiation exposure in laryngeal squamous cell carcinoma (LSCC). A lentivirus vector containing the LAMP3 gene was transfected into HEp-2 cells to construct siRNA-LAMP3 and complementation (siLAMP3+LAMP3) groups. Treatment with 4 Gy or 8 Gy radiation was administered to evaluate the role of LAMP3 in radiation therapy. Apoptosis was detected by Annexin V/propidium iodide double staining. Cell migration and invasion were measured in vitro using Transwell and Matrigel assays. Downstream genes regulated by LAMP3 were analyzed using RNA sequencing. Furthermore, a patient-derived xenograft (PDX) model of LSCC was established to verify the efficacy of radiation exposure and the associated signaling pathways downstream of LAMP3. The efficacy of radiation showed that cell proliferation was significantly inhibited by siRNA-LAMP3 knockdown. Increased apoptosis was also observed. Notably, the inhibitory effect was attenuated and apoptosis rates were decreased after LAMP3 complementation. In vitro cellular assays showed that migration and invasion were significantly suppressed by siRNA-LAMP3 knockdown and increased after LAMP3 complementation. Analysis of the efficacy of radiation exposure in the PDX model showed that LAMP3-specific knockdown inhibited tumor growth and that tumor growth was further reduced by the combined radiotherapy treatment. According to transcriptome analysis, the extracellular matrix-receptor interaction pathway is regulated by LAMP3, and further analysis revealed significant differences in key-associated molecules, including laminin subunit gamma-2 (LAMC2) and tenascin-C (TNC). Validation of the in vivo PDX model using qPCR and Western blot analyses supported the abovementioned results. The present findings suggest that reduced LAMP3 expression enhances the efficacy of radiation exposure in LSCC by regulating the LAMP3/LAMC2/TNC signaling pathway. Impact statement: It is important to establish effective early diagnostic indicators and reliable treatment strategies for laryngeal squamous cell carcinoma (LSCC). We previously found that expression of LAMP3 was significantly higher in cancerous tissues compared to adjacent normal surgical margin tissues. The present study explored the role of LAMP3 and the related molecular mechanisms in the efficacy of radiation exposure in LSCC. In vitro Transwell and Matrigel assays were performed, and a patient-derived xenograft (PDX) model of LSCC was established. Associated signaling pathways downstream of LAMP3 were analyzed using RNA sequencing. Signaling pathways regulated by LAMP3 were clearly identified by combining the PDX model with transcriptome analysis. Reduced LAMP3 expression enhanced the efficacy of radiation exposure in LSCC. Thus, by utilizing this molecule as a marker, specific groups of patients may be screened for targeted therapy in the future.